Does Collective Action Sequester Carbon? : The Case of the Nepal Community Forestry Program - Bluffstone, Randy; Somanathan, Eswaran; Jha, Prakash; Luintel, Harisharan; Bista, Rajesh; Paudel, Naya; Adhikari, Bhim (World Bank, Washington, DC, 2015)
This paper estimate the effects of collective action in Nepal’s community forests on four ecological measures of forest quality. Forest user group collective action is identified through membership in the Nepal Community Forestry Programme, pending membership in the program, and existence of a forest user group whose leaders can identify the year the group was formed. This last, broad category is important, because many community forest user groups outside the program show significant evidence of important collective action. The study finds that presumed open access forests have only 21 to 57 percent of the carbon of forests governed under collective action. In several models, program forests sequester more carbon than communities outside the program. This implies that paying new program groups for carbon sequestration credits under the United Nations Collaborative Programme on Reducing Emissions from Deforestation and Degradation in Developing may be especially appropriate. However, marginal carbon sequestration effects of program participation are smaller and less consistent than those from two broader measures of collective action. The main finding is that within the existing institutional environment, collective action broadly defined has very important, positive, and large effects on carbon stocks and, in some models, on other aspects of forest quality.